1991
DOI: 10.1113/jphysiol.1991.sp018874
|View full text |Cite
|
Sign up to set email alerts
|

Three types of bovine chromaffin cell Ca2+ channels: facilitation increases the opening probability of a 27 pS channel.

Abstract: SUMMARY1. Cell-attached patch recordings from bovine chromaffin cells were performed with 90 mM-Ba2`in the patch pipette and with isotonic potassium aspartate in the bathing solution to zero the membrane potential. Three different types of unitary Ca2l channel activity could be distinguished in these recordings.2. A 27 pS Ca2" channel was distinguished by constructing amplitude histograms and measuring slope conductance. This channel activated over a broad range of potentials (depolarizations > -10 mV).3. A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 33 publications
2
44
2
Order By: Relevance
“…In all cells, the voltage-gated Ca 2ϩ current showed typical inactivation during a train (Fig. 2 B; comparison of first and last current), with no evidence for activation of additional "facilitation" channels as described for calf chromaffin cells (Artalejo et al, 1991(Artalejo et al, , 1994.…”
Section: Characteristics Of Exocytosis With Enhanced Ca 2؉ Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…In all cells, the voltage-gated Ca 2ϩ current showed typical inactivation during a train (Fig. 2 B; comparison of first and last current), with no evidence for activation of additional "facilitation" channels as described for calf chromaffin cells (Artalejo et al, 1991(Artalejo et al, , 1994.…”
Section: Characteristics Of Exocytosis With Enhanced Ca 2؉ Efficacymentioning
confidence: 99%
“…The early rapidly decaying inward component is a Na ϩ current. The Ca 2ϩ current inactivates during all three stimulus trains, and there is no evidence for recruitment of a "facilitation" current (Artalejo et al, 1991). C, Percentage of cells that responded to a given stimulus protocol with a Ca 2ϩ efficacy that was enhanced relative to the standard transfer f unction.…”
Section: Characteristics Of Exocytosis With Diminished Ca 2؉ Efficacymentioning
confidence: 99%
“…In the hippocampus, dihydropyridine-sensitive calcium channels have been observed that are active at very negative potentials following maintained depolarization (Fisher, Gray & Johnston, 1990). Whether this activity results from a specific kind of calcium channel, as in chromaffin cells (Artalejo et al 1991), or is due to potentiation of the standard L-type calcium channel (Fisher et al 1990) remains unclear.…”
mentioning
confidence: 99%
“…Although such changes are often associated with the NMDA receptor channel (Malenka, Kauer, Perkel & Nicoll, 1989), there is also evidence suggesting that voltage-gated calcium channels are involved (Pitler & Landfield, 1990;Moyer, Thompson, Black & Disterhoft, 1992;Johnston, Williams, Jaffe & Gray, 1992). For example, there are 'facilitation' calcium channels in adrenal chromaffin cells that show greatly increased activity subsequent to large depolarizations (Artalejo, Mogul, Perlman & Fox, 1991).…”
mentioning
confidence: 99%
“…Both are affected by VDCCs ␤ subunits but in opposite ways. One type, observed in several neuronal cells 1,23,26) , is displayed by L-type VDCCs and has been recapitulated in Xenopus oocytes injected with cDNAs encoding the ␣ 1C and a ␤ subunit 6) . Another type of prepulse facilitation, also referred to as prepulse potentiation, is seen primarily in non-L-type VDCCs of neurons and is caused by a reversal or attenuation of the inhibition of channel activity imposed by agonists known to act via Gi/Go-type-Gprotein-coupled receptors and formation of a free G-protein ␤␥ dimmer 10,12,19,37) .…”
Section: Introductionmentioning
confidence: 99%